2018
DOI: 10.1001/jama.2018.1525
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Mortality in the United States

Abstract: Infectious disease is distinguished from most other fields of medicine by constant and rapid change. As microorganisms emerge, new treatment and prevention strategies also evolve. Although much progress has been made, infections remain a major and often preventable cause of death worldwide.In this issue of JAMA, el Bcheraoui and colleagues 1 report mortality trends for major infectious diseases in the United States, both nationally and at the county level, using data from the National Center for Health Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are dozens of specialized disciplines that can effectively describe a component of the system, but complex problems exist where biology and ecology have become entangled with economics, social expectations, and politics. Hierarchical leadership that seeks simple solutions and paternalistic environmental management have made progress in some areas such as management of infectious diseases (Shuman & Malani, 2018) but the drivers of complex problems have worsened (Waltner-Toews, 2017). Economic inequities, loss of biodiversity, and ecological degradation are increasing, and ecosystems are showing signs of being unable to meet the needs of the lives (human and non-human) occupying them (Hassan et al, 2005).…”
Section: Literaturementioning
confidence: 99%
“…There are dozens of specialized disciplines that can effectively describe a component of the system, but complex problems exist where biology and ecology have become entangled with economics, social expectations, and politics. Hierarchical leadership that seeks simple solutions and paternalistic environmental management have made progress in some areas such as management of infectious diseases (Shuman & Malani, 2018) but the drivers of complex problems have worsened (Waltner-Toews, 2017). Economic inequities, loss of biodiversity, and ecological degradation are increasing, and ecosystems are showing signs of being unable to meet the needs of the lives (human and non-human) occupying them (Hassan et al, 2005).…”
Section: Literaturementioning
confidence: 99%
“…Infectious diseases differ from non-communicable ones as they evolve with changing pathogenic strains and the emergence of antibiotic resistance. Ongoing research aims to counteract the acquisition of resistance genes in new bacteria and adapt to shifting susceptibility patterns [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…With microorganisms emerging new preventions and treatments evolve as well. It has been reported that almost 25% of the population experienced 2-3 episodes of infection every year (Shuman et al, 2018). Many foods primarily deteriorate because of microbes that give rise to the loss of quality and safety, on which people worldwide are concerning more because foodborne diseases are subject to outbreak due to pathogenic and spoilage microorganisms in foods (Rawat, 2015).…”
Section: Introductionmentioning
confidence: 99%